PENGARUH SISTEM AKUNTANSI PERTANGGUNGJAWABAN DALAM EFEKTIVITAS LAPORAN KEUANGAN TERHADAP KINERJA PERUSAHAAN DI BURSA EFEK INDONESIA - Liana, Dinda; Prima, Argo Putra (LPPM Universitas Putera Batam, 2020)
All companies try to put themselves into the best to achieve its goals. However, there is still a lot of processing accountability reports in obtaining income and expenses that are not effective to make the company's performance decline. Then this study aims to determine the effect of the responsibility accounting system in the effectiveness of financial statements on the performance of companies on the Indonesia Stock Exchange in the period 2015-2019. This type of research is quantitative descriptive. The population in this study amounted to 26 companies with criteria of manufacturing companies in the consumer industry industry sector and 130 samples. Sampling using purposive sampling. Data collection techniques in this study using documentation and study of literature. Data analysis techniques used are descriptive analysis, classic assumption tests, multiple linear regression, hypothesis testing, and the coefficient of determination. Hypothesis test results Fcount 616,894 ˃ Ftable 3.07 and a significant level of F value 0.00 < 0.05 then Ho is rejected and Ha is accepted. It can be said that the accounting system for accountability in the effectiveness of financial statements together has a significant influence on company performance. And the results of the determination coefficient R Square of 9.07%. The conclusion is that the value of the responsibility accounting system variable and the effectiveness variable of the financial statements affect the company's performance by 90.7% and the remaining 9.3% is influenced by other variables not in this study.